Price Linkage Between Milling and Feed Wheat Prices in Poland and Germany - Hamulczuk, Mariusz; Łopaciuk, Wiesław (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2013)
The aim of the paper was to analyse spatial price transmission in the wheat market in Poland and Germany. The analysis was conducted with the use of weekly milling and feed wheat price series and cointegration framework. The results confirm high linkage between prices in Poland and Germany as well as allow us to identify Germany as the price-leading market. However, as the self-sufficiency in the German wheat market has deteriorated, there are signals of growing importance of the Polish market in the milling wheat price formation.